Thiel, Markus (ed.). The „Militant Democracy“ Principle in Modern Democracies - Tomáš Blažek (Časopis pro Právní Vědu a Praxi, 2011)
Recenze publikace - Thiel, Markus (ed.). The „Militant Democracy“ Principle in Modern Democracies Ashgate, 2009, 438 str., ISBN: 978-0-7546-7183-1